Incidence and Outcome of Severe and Nonsevere Thrombocytopenia Associated With Zika Virus Infection—Puerto Rico, 2016. (3rd December 2018) - Van Dyne, Elizabeth A; Neaterour, Paige; Rivera, Aidsa; Bello-Pagan, Melissa; Adams, Laura; Munoz-Jordan, Jorge; Baez, Priscilla; Garcia, Myriam; Waterman, Stephen H; Reyes, Nimia; Richardson, Lisa C; Rivera-Garcia, Brenda; et al.
Abstract: Background: Zika virus (ZIKV) infection has been associated with severe thrombocytopenia. We describe the incidence, clinical manifestations, and outcomes of patients with ZIKV infection and thrombocytopenia. Methods: We reviewed medical records of patients with ZIKV infection and thrombocytopenia (platelet count <100 ×10 9 cells/L) in Puerto Rico during 2016. Severe thrombocytopenia was defined by platelet count <20 ×10 9 /L or a platelet count <50 ×10 9 /L and treatment for immune thrombocytopenia (ITP). Results: Of 37 878 patients with ZIKV infection, 47 (0.1%) had thrombocytopenia in the absence of an alternative etiology (1.4 cases/100 000 population), including 12 with severe thrombocytopenia. Most patients with thrombocytopenia were adult (77%) and male (53%). Platelet nadir occurred a median (range) of 6 (1–16) and 5 (0–34) days after symptom onset for patients with severe and nonsevere thrombocytopenia, respectively. Among patients with severe thrombocytopenia, all had bleeding, 33% were admitted to the intensive care unit, and 8% died; 50% were treated for ITP. Among 5 patients with severe thrombocytopenia who received intravenous immunoglobulin, the median platelet count increase (range) was 112 (65–202) ×10 9 /L. In contrast, among 4 patients who received platelet transfusion, the median increase in platelet count (range) was 8.5 (–6 to 52) ×10 9 /L. Conclusions: Patients with severe thrombocytopenia and ZIKV infection experienced prominent acute morbidity. Consistent with recommended management, administration of ITP treatments to such patients may be more efficacious than platelet transfusion in resolving thrombocytopenia. Severe thrombocytopenia should be considered a rare outcome of ZIKV infection.